Phosphoserine Aminotransferase Pathogenetic Variants in Serine Deficiency Disorders: A Functional Characterization - Francesco Marchesani; Annalisa Michielon; Elisabetta Viale; Annalisa Bianchera; Davide Cavazzini; Loredano Pollegioni; Giulia Murtas; Andrea Mozzarelli; Stefano Bettati; Alessio Peracchi; Barbara Campanini; Stefano Bruno (Biomolecules, 2023)
In humans, the phosphorylated pathway (PP) converts the glycolytic intermediate D-3-phosphoglycerate (3-PG) into L-serine through the enzymes 3-phosphoglycerate dehydrogenase, phosphoserine aminotransferase (PSAT) and phosphoserine phosphatase. From the pathogenic point of view, the PP in the brain is particularly relevant, as genetic defects of any of the three enzymes are associated with a group of neurometabolic disorders known as serine deficiency disorders (SDDs). We recombinantly expressed and characterized eight variants of PSAT associated with SDDs and two non-SDD associated variants. We show that the pathogenetic mechanisms in SDDs are extremely diverse, including low affinity of the cofactor pyridoxal 5′-phosphate and thermal instability for S179L and G79W PSAT, loss of activity of the holo form for R342W PSAT, aggregation for D100A PSAT, increased Km for one of the substrates with invariant kcats for S43R PSAT, and a combination of increased Km and decreased kcat for C245R PSAT. Finally, we show that the flux through the in vitro reconstructed PP at physiological concentrations of substrates and enzymes is extremely sensitive to alterations of the functional properties of PSAT variants, confirming PSAT dysfunctions as a cause of SSDs.